Supernatural. Season seven [videorecording (DVD)] - Padalecki, Jared, 1982-; Ackles, Jensen (Warner Home Video, 2012)
Sam and Dean fight demons. Real demons, like Lucifer, who tortures Sam with visions of Hell. Private demons, as the brothers face a traumatic personal loss when Bobby is cut down by alien forces. And as Sam and Dean travel the back roads of America, hunting monsters who wreak havoc on the innocent, a new and more terrible foe hunts them: Leviathans, freed from Purgatory and immune to the brothers' arsenal of weapons and cunning. With Bobby gone, all Sam and Dean can rely on is each other.